Moderating Role of Environmental Settings in Relationship Between Product Innovativeness and Its Performance During the Launch - Brazauskaitė Indrė; Auruškevičienė Viltė (Economics and Business, 2017)
The current research depicts the relationship between new product innovativeness and its performance, which was addressed in previous studies; yet the results remain contradictive with little focus on environmental settings. The paper aims to reveal the role of commercial environment towards new product performance, which allows forecasting the performance on the basis of expected settings and exploring the link between new product innovativeness and its performance in a more detailed way. In the study, moderating environmental settings are defined as a set of marketplace characteristics on market level, company commercial characteristics, and a set of sales channel characteristics on retailer’s category level. Research contributes to the following areas: reveals the role of environment towards performance and allows forecasting new product performance on the basis of expected settings.